PELATIHAN PEMBUATAN KERAJINAN TANGAN MENGGUNAKAN LIMBAH RUMAH TANGGA (SAMPAH PLASTIK) DI KELURAHAN NIKAN JAYA KECAMATAN LUBUKLINGGAU TIMUR I - Yeni Trianah; Santi Sani (LP4MK STKIP PGRI Lubuklinggau, 2020)
This activity aims to provide training and skills to the community of the Nikan Jaya village in utilizing plastic waste into handicrafts with high economic value. This activity was carried out from March 2020 which included socialization, training, coaching, and evaluation. This activity was attended by 20 participants consisting of groups of young women and housewives. Participants came from the village of Nikan Jaya and its surroundings. This training uses a Forum Group Discussion approach. The socialization provided includes the negative impact of plastic waste on the environment, various potential uses of plastic waste, activities followed by demonstrations of making handicrafts. Then proceed with training on making handicrafts. The results of the survey showed that the participants were very enthusiastic and gave a fairly good response during the activity as well as after. In addition, there is a request to continue coaching until the participants are really skilled at making handicrafts.